2017
DOI: 10.1002/pbc.26859
|View full text |Cite
|
Sign up to set email alerts
|

Local therapy to distant metastatic sites in stage IV rhabdomyosarcoma

Abstract: Local treatment to all metastatic sites was associated with improved PFS and OS at 5 years. The use of WLI improved pulmonary control in patients with lung metastasis. We recommend an aggressive approach including local therapy to DMS in children with stage IV RMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…For instance, Texas Children’s Hospital analysis of local therapy to metastases in stage IV rhabdomyosarcoma revealed a LC of 73% at a median follow-up of 2 years after irradiation of nonlung or nonbone marrow metastatic sites. 12 The majority of lesions in the above series received a total of 50.4 Gy in 28 fractions. Similarly, Kandula et al studied outcomes after irradiation of metastatic sites in patients with stage IV neuroblastoma and observed 23% local failures in 13 metastatic sites treated with at least 12 fractions of conventional RT to a median dose of 21.6 Gy.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…For instance, Texas Children’s Hospital analysis of local therapy to metastases in stage IV rhabdomyosarcoma revealed a LC of 73% at a median follow-up of 2 years after irradiation of nonlung or nonbone marrow metastatic sites. 12 The majority of lesions in the above series received a total of 50.4 Gy in 28 fractions. Similarly, Kandula et al studied outcomes after irradiation of metastatic sites in patients with stage IV neuroblastoma and observed 23% local failures in 13 metastatic sites treated with at least 12 fractions of conventional RT to a median dose of 21.6 Gy.…”
Section: Discussionmentioning
confidence: 89%
“…Similar outcomes have been reported in studies where standard fractionation was used to treat metastatic sites. 12, 15, 21 In an analysis of survival after conventional RT for metastatic ES in children, Paulino et al reported 2-year rates for OS and PFS at 30.3% and 23.3%. 21 Rahn and colleagues observed a median survival of 6.5 months after palliative RT to the metastatic lesions in a cohort of 44 children with different primary malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In childhood RMS, treatment and prognosis vary widely according to a series of clinical characteristics such as histology and fusion status, having fusion-positive RMS patients a worse outcome compared to fusion-negative ones [24][25][26]. Distal metastases remains the most adverse prognostic factor despite continuous improvement of the diagnostic capabilities and the use of more intense treatments [27][28][29]. Within this group of patients, outcome further differs significantly when multiple risk factors are combined, such as patient's age, primary tumor site, number of metastases, and bone or bone marrow involvement [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy in combination with chemotherapy is an effective modality for treatment of lung metastases in pediatric tumors 1,2. Stereotactic body radiotherapy (SBRT) delivers conformal and ablative treatment in 1–5 fractions, while sparing the volume of heart and lung irradiated.…”
Section: Introductionmentioning
confidence: 99%